Concepts in male health perspectives across the lifespan - Leone, James E., 1976- (Public health/aahe ;, 2012)
"This important resource offers a practical approach to understanding the health of males of all races, ethnicities, socioeconomic status, cultures, ages, and orientations. It provides solid guidance for males to optimize their well-being and prevent illness and impairment. Each chapter of this book comprehensively reviews an important dimension of a male health and examines the contributing epidemiological, historical, psychosocial, cultural/ethical, legal, political, and economic influences. It is ideal for programs in health education, public health, community health nursing, and other health sciences. The diverse range of topics will allow for complete coverage ranging from body and sexuality to aggression and occupational health"--